Implementation of Differentiation Learning In SMK Negeri 9 Padang - Aninda, Femira Nasyirah; Siregar, Juliana; Elida, Elida; Yasih, Fitri (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research was motivated by the discovery of different learning styles and characteristics of students, which became a challenge for culinary teachers. This research aims to describe the process of implementing differentiated learning in the culinary skills program at SMK Negeri 9 Padang starting from the initial stages, implementation, to evaluation. This type of research is descriptive research with a qualitative approach using the case study method. The informants for this research were 5 culinary teachers at SMK Negeri 9 Padang. The technique for taking informants uses the Purposive Sampling technique. Data collection techniques are carried out by conducting interviews, observation and documentation. In order to increase the accuracy of the data, the author tested the validity of the data by means of data triangulation. Next, the data is analyzed by collecting the data obtained, reducing the data, presenting the data, and drawing conclusions. The research results show that the initial stage of differentiated learning is carried out by planning lessons, teachers also attend various training and seminars to increase their skills and knowledge in implementing differentiated learning. The implementation of differentiated learning is divided into several activities according to the teaching module design. These learning activities are differentiated based on three components, namely content differentiation in the form of involving students in group assignments; process differentiation in the form of the use of learning video teaching media, textbooks, oral explanations, as well as the formation of study groups, and product differentiation in the form of practice with groups with different products so that students can learn from other groups, presentations in front of the class, and individual assignments. Evaluation of differentiated learning is carried out by teachers with assessments which include assessments at the beginning of the learning process, assessments during the learning process, and assessments at the end of learning which are used to see students' abilities in understanding and remembering lesson material.